Effects of Overtraining on Skeletal Muscle Growth and Gene Expression - Xiao, W.; Chen, P.; Dong, J. (International Journal of Sports Medicine, 2012)
The aim of this study was to investigate the effects of overtraining on skeletal muscle growth and growth-related gene expression. The rats of overtraining group (OT) and overtraining recovery group (OTR) were subject to 11 experimental weeks of overtraining protocol. It was found that the absolute gastrocnemius muscle wet weight of the OT group was significantly lower than that of the sedentary group (23.6%, P<0.01). Serum creatine kinase was significantly higher in the OT and OTR groups than the sedentary group. CD68, CD163, MyoD, myogenin, IL-1β, TNF-α, IGF-I and MGF mRNA did not change in the OT group as compared with the sedentary group. IL-6 and TGF-β1 mRNA in the OT group increased significantly as compared with the sedentary group (2.17 fold and 1.78 fold, respectively; P<0.01). IL-10 mRNA decreased significantly in the OT group (63%, P<0.01) and the OTR group (77%, P<0.01) compared to the sedentary group. COX-2 mRNA decreased significantly in the OT group (60%, P<0.01) and the OTR group (69%, P<0.01) from the sedentary group. uPA mRNA in the OT group was significantly lower than that in the sedentary group (32%, P<0.01). These data suggest that inflammatory cytokines, COX-2 and uPA may play roles in the inhibition of skeletal muscle growth induced by overtraining.
Keywords: overtraining; skeletal muscle; growth; cyclooxygenase-2; urokinase-type plasminogen activator; inflammatory cytokines